THEORETICAL STUDY OF LEGAL PROTECTION FOR CREDITORS IN THE OPEN SAVINGS ACCOUNT STANDARD AGREEMENT IN BANKS IN INDONESIA - Dauri Dauri; Nadya Waliyyatunnisa; Retias Dewi Jayanti (Legal Standing : Jurnal Ilmu Hukum, 2020)
This study aims to examine the legal protection of creditors against standard savingsbookkeeping agreements at the Bank. With the enactment of Law Number 8 of 1999concerning Consumer Protection, the customer or customer gets legal protection. To bea customer at a bank, the community must first be bound in a legal relationship with thebank. The legal relationship between the customer and the bank occurs after bothparties sign an account opening form as proof that the customer has agreed and iswilling to fulfill the terms and conditions proposed by the bank. Customers who deposittheir money in the bank expect profit, security and convenience, therefore there must beprotection provided by the bank to depositors. The problem that will be discussed in thisresearch is how the form of legal protection for creditors against the standardagreement to open a savings account at a bank. The method used in this study is a typeof normative juridical research or literature review or documents related to theproblem. Based on the results of the study the authors found that the form of legalprotection for deposit customers against the exoneration clause in the form of opening a savings account at a commercial bank is one of the government's efforts to protect consumers against businesses in the financial services sector. Financial ServicesAuthority Regulation Number:1/POJK.07/2013 concerning Consumer Protection TheFinancial Services Sector is able to put the position of consumers of financial servicesin balance with financial service players, but in practice banks still apply theexoneration clause.